TINJAUAN YURIDIS TINDAK PIDANA PEMBUNUHAN YANG DILAKUKAN DENGAN RENCANA (PUT.108/PID.B/2020/PN.RHL): Juridical Review of The Crime of Murder Commited with a Plan (Study of Decision Number 109/Pid.B/2020/PN.RHL) - Akbar, Muhammad Fakhri Zaki; Tawang, Dian Adriawan Daeng (AMICUS CURIAE, 2024)
This research is entitled Juridical Review of the Crime of Murder Committed with a Plan (Put No.109/Pid.B/2020/PnRhl). There are 2 (two) main issues raised in this thesis, namely how the perpetrator'sactions comply with the elements of the offense in Article 340 of the Criminal Code and how the basis forjudges in deciding criminal cases of murder. This research is a juridical-normative research, the natureof the research is descriptive-analytical, data collection uses secondary data and primary materials, thisdata is carried out through library research methods. The actions carried out by the perpetrators are notappropriate if they are terminated by Article 338 of the Criminal Code concerning ordinary Murder,because the actions of the perpetrators were carried out with a prior plan in committing the Criminal Actof Murder, therefore the more appropriate Article to be used by the perpetrators is Article 340 of theCriminal Code concerning Murder which carried out with a plan in advance because the perpetrator'sactions have fulfilled the elements of the offense of Article 340 of the Criminal Code.